Patient Empowerment Dan Self-Management Pada Pasien Diabetes Mellitus Tipe 2 - Muhammad Abiyoso Ramadhan (Jurnal Ilmiah Kesehatan Sandi Husada, 2019)
Diabetes mellitus is a metabolic disease were hyperglycemia happens. This is caused by abnormality of insulin production or the distribution. Diabetes mellitus prevalention has increased till now all over the world including in Indonesia. Depends on Basic Health Research (RISKESDAS), prevalention of diabetes mellitus at 2018 increased 2,6% compared to 2013 and reach 14 millions of life. Diabetes mellitus is not only health problems, it also about behaviour and lifestyle. Diabetes mellitus could happens due to unhealthy behaviour and lifesytle. Therefore diabetes mellitus patient be required some approach were able to change patient behaviour and lifestyle. Patient empowerment and self-management is an approach that could change patient behaviour and lifestyle.